Experimental and numerical study of mass transfer efficiency in new wire gauze with high capacity structured packing. Issue 16 (2nd November 2019) - Amini, Younes; Karimi-Sabet, Javad; Nasr Esfahany, Mohsen; Haghshenasfard, Masoud; Dastbaz, Abolfazl
ABSTRACT: Experimental and numerical studies were conducted on the mass transfer efficiency of new wire gauze structured packing. For serving this purpose, various operational conditions were studied to assess the optimal parameters such as HETP of PACK-2100 in the distillation column. The results indicate that the HETP values are enhanced in comparison to conventional ones. In addition, the HETP slowly increases from 4 to 6 cm as mass flow rates of air and liquid flow are increased. The numerical simulations were also performed to describe the performance of the PACK-2100. The Eulerian-Eulerian multiphase approach is applied to calculate the value of HETP and pressure drop. The computational results confirmed that our experimental results. The average relative error between CFD predictions and the experimental data for the prediction of mass transfer efficiency is 20.45%.